Visible light-active hybrid film photocatalyst of polyethersulfone–reduced TiO2: photocatalytic response and radical trapping investigation - Mohd Hir, Zul Adlan (Springer, 2018)
The present work emphasizes the facile synthesis and characterization of reduced TiO2–polyethersulfone and evaluation of its visible light photocatalytic response. Reduced TiO2 (rTiO2) was prepared by a simple thermal reduction of NaBH4 at 300 °C for 50 min before immobilized into polyethersulfone polymer film via phase inversion. X-ray diffraction, scanning electron microscopy and energy-dispersive X-ray characterization showed the photoactive rTiO2 was still intact onto the PES with homogeneous dispersion after the preparation process. The incorporation of rTiO2 was observed to improve the hydrophilicity and film’s surface roughness up to 7.03 nm. X-ray photoelectron spectroscopy confirmed the formation of interstitial site of rTiO2 at lower binding energies of 456.1 and 461.8 eV, which extends visible light absorption by either the existence of Ti3+ species or oxygen vacancies. The low band gap (2.85 eV) of the film photocatalyst synergistically envisages the best degradation performance at 13 wt% of rTiO2 loading by degrading 100% methyl orange in acidic conditions. Based on pseudo-first-order kinetic model, the highest degradation rate constant of 1.41 × 10−3 min−1 was obtained with ·O2− acted as the main active species during the process. The reusability studies revealed that the film photocatalyst could be repeatedly used for up to five times without severe deactivation.